Operational optimization of a 4th generation district heating network with mixed integer quadratically constrained programming - Hering, Dominik; Faller, Michael R.; Xhonneux, André; Müller, Dirk (Energy (Oxford), 2022)
Decreasing CO2-Emissions is a common goal for efficient energy system design and operation. An efficient design for the heating sector are 4th-generation district heating networks with waste heat integration. This paper focuses on operational optimization of a 4th-generation district heating network with regards to temperatures and use of thermal inertia in the network and in thermal energy storages. A case study is presented, where the system is formulated as a Mixed-Integer Quadratically Constrained Program. The quadratic formulations allow to simultaneously optimize energy balances and temperatures, with regards to efficiency correlations and temperature thresholds of components. The case study consists of seven consumers with heat pumps and thermal energy storages, which are supplied by waste heat from a nearby high-performance computer. The case study is solved for eight representative days. The results show, that savings in operational costs up to 18.2% compared to a reference system with constant temperatures are possible. All in all, this paper demonstrates the use and limitations of quadratic formulations in an operational optimization and emphasizes the possibility of temperature optimizations in operation of 4th-generation district heating. •An MIQCP is presented for optimization of load shifting and operating temperatures.•The method is applied to a low temperature district heating network.•Results are compared to fixed temperature reference scenarios.•Including temperatures in the optimization improves the objective.